2017
DOI: 10.3390/met7040121
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NbC Addition on the Sintering Behaviour of Medium Carbon PM Steels

Abstract: Abstract:In this work, the effects of NbC additions on the microstructure and mechanical properties were examined. In order to do this, NbC compounds were added into the Fe matrix at the weight percentage of 0.1-2 with individually to obtain powder mixture. The microstructure of the powder metallurgy (PM) steels were characterized by optic microscope, scanning electron microscope (SEM) and energy dispersive spectroscopy (EDS). Experimental results indicated that NbC alloyed steels can be produced by PM technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
4
17
0
Order By: Relevance
“…Sintering is used to combine particles to each other in a certain temperature and time. Similar studies agree with this result [5][6][7]15]. Table 3.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Sintering is used to combine particles to each other in a certain temperature and time. Similar studies agree with this result [5][6][7]15]. Table 3.…”
Section: Resultssupporting
confidence: 82%
“…The results indicated that the effect of niobium in dispersion strengthening is higher than that of vanadium. Niobium also increases the strength more than vanadium by increasing the pearlite ratio and forming small grains [6,7]. …”
Section: Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature [28,29], in studies on determining the effect of Ni addition on the mechanical properties of steels, it is seen that the high Ni content in post-quenching processes decreases the strength as it causes residual austenite. Additionally, in powder metallurgy studies [30,31] it has been reported to decrease strength, as excess alloy content causes porosity. However, in studies without heat treatment, the addition of Ni has increased the strength somewhat.…”
Section: Resultsmentioning
confidence: 99%
“…With every new research and innovations, alloy steels continue to meet the needs. The alloy steel is commonly employed in several sectors, namely, aircraft industry, auto industry, and structures (bridges, buildings) [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%